Bullous Sweet's syndrome with figurate erythema and cutaneous hemophagocytosis - Shiang-Yu Yang; Chih-Hung Lin; Chung-Hsing Chang (Wolters Kluwer Medknow Publications, 2017)
A 56-year-old woman presented with multiple blisters on the rim of painful erythematous annular lesions over the trunk and four extremities, accompanied with fever and arthralgia on both ankles and feet. Laboratory studies showed neutrophilia and elevated C-reactive protein level. Skin biopsy revealed exuberant edema of the papillary dermis, extensive neutrophil infiltration, and hemophagocytosis within the dermis. Her symptoms and skin lesions resolved 3 days after initiation of systemic corticosteroids. To the best of our knowledge, this is the first case report of cutaneous hemophagocytosis without additional symptoms of hemophagocytic syndrome in patients with Sweet's syndrome.